Rho kinase-1 mediates cardiac fibrosis by regulating fibroblast precursor cell differentiation - Haudek, Sandra B.; Gupta, Damon; Dewald, Oliver; Schwartz, Robert J.; Wei, Lei; Trial, Joann; Entman, Mark L. (Cardiovascular Research, 2009)
AimsHighly proliferative, CD34+/CD45+ fibroblasts derived from monocytic, blood-borne precursor cells play a critical role in the development of fibrosis in a murine ischaemic/reperfusion cardiomyopathy (I/RC) model. The differentiation of human monocytes into fibroblasts in vitro occurs after transendothelial migration (TEM) induced by monocyte chemoattractant protein 1 (MCP-1). Because Rho-associated kinase-1 (ROCK-1) has been implicated in fibrosis and leukocyte TEM, we investigated its involvement in I/RC.Methods and resultsWe subjected mice with genetic deletion of ROCK-1 to I/RC. We found that ROCK-1-/- mice did not develop the fibrosis and cardiac dysfunction characteristic for I/RC: compared with wild-type, ROCK-1 -/- hearts showed markedly lower numbers of I/RC-induced α-smooth muscle actin+ fibroblasts and CD34+/ CD45+ fibroblast precursors. Isolated cardiac fibroblasts from ROCK-1-/- mice undergoing I/RC were large and slowly proliferating, similar to fibroblasts isolated from sham-treated hearts. We also performed in vitro assays in which human peripheral blood mononuclear cells (PBMC) migrated through endothelial cells in response to MCP-1. Prior to migration, PBMC were incubated with ROCK-1-targeting small interfering RNA to silence ROCK-1 expression. We found that an 80 reduction of ROCK-1 protein did not inhibit TEM, but significantly reduced the amount of mononuclear cells that differentiated into fibroblasts by >20-fold.ConclusionOur data implicate an important role for ROCK-1 in the differentiation, but not in the TEM of monocytes that mature into cardiac fibroblasts. These cells mediate non-adaptive fibrosis.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac fibroblasts; Endothelial transmigration; Fibrosis; Monocytes; Rho-associated kinase-1